Restoring lost land in Cameroon - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Researcher Oscar Eyog Matig explains how intercropping of trees and cereal crops, combined with water harvesting, has restored degraded land in north Cameroon.